Решите уравнение: 1) 2х - х-2/2 = х/3 - 6    2) 1-у/7 + у = у/2+3    3) 0,69 = 5-2у/8 *13.8

Решите уравнение: 1) 2х - х-2/2 = х/3 - 6    2) 1-у/7 + у = у/2+3    3) 0,69 = 5-2у/8 *13.8
Гость
Ответ(ы) на вопрос:
Гость
1) 2х - х-2/2 = х/3 - 6 6*2х-3(х-2)=2х-6*6 12х-3х+6=2х-36 9х+6=2х-36 9х-2х=-36-6 7х=-42 х=-42:7 х=-6 2) 1-у/7 + у = у/2+3   2(1-у)+14у=7у+14*3 2-2у+14у=7у+42 2+12у=7у+42 12у-7у=42-2 5у=40 у=40:5 у=8 3) 0,69 = 5-2у/8 *13.8 5-2у/8=0,69:13,8 5-2у/8=0,05 5-2у=0,05*8 5-2у=0,4 -2у=0,4-5 -2у=-4,6 у=-4,6:(-2) у=2,3
Не нашли ответ?
Ответить на вопрос
Похожие вопросы